2005
DOI: 10.1002/pssb.200590013
|View full text |Cite
|
Sign up to set email alerts
|

Structure and transport properties of coherently strained La2/3Ca1/3MnO3/SrTiO3 superlattices

Abstract: The front cover of this issue, taken from the Editor's Choice, displays the structural characterization of coherently strained La2/3Ca1/3MnO3/SrTiO3 superlattices prepared by laser molecular beam epitaxy [1]. The pronounced superlattice Bragg peaks and the Kiessig fringes indicate an excellent superlattice structure. The superlattice modulation period is obtained by fitting sin2 θ ∼ n2 and also specular low‐angle X‐ray reflectivity. The correlated interface roughness is confirmed by offset low‐angle X‐ray refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As it has been shown in several studies [1,2], the tension of the films due to mismatch with the substrate is the reason for the change in the electric and magnetic parameters of the films. It was shown that the three-dimensional compression of the crystal lattice increases the hopping probability amplitude in the double exchange model, which leads to an increase in the Curie temperature (TC), while the biaxial distortions of the Jahn-Teller type cause an increase in the localization of the electrons and decrease TС [3,4].…”
mentioning
confidence: 99%
“…As it has been shown in several studies [1,2], the tension of the films due to mismatch with the substrate is the reason for the change in the electric and magnetic parameters of the films. It was shown that the three-dimensional compression of the crystal lattice increases the hopping probability amplitude in the double exchange model, which leads to an increase in the Curie temperature (TC), while the biaxial distortions of the Jahn-Teller type cause an increase in the localization of the electrons and decrease TС [3,4].…”
mentioning
confidence: 99%